ASSESSING LEARNER AUTONOMY IN EFL LEARNING: INSIGHTS FROM THAI SENIOR HIGH SCHOOL STUDENTS - Boonma, Nida; Swatevacharkul, Rosukhon (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
Raising learners’ awareness of the need to develop their capacity to learn autonomously has been one of the primary educational goals worldwide. Autonomy development is thus crucial for preparing high school students for higher education. However, only limited studies are available on assessing learner autonomy within English learning education for Thai senior high school students. Therefore, this study aimed to assess learner autonomy in English learning as perceived by Thai senior high school students in public schools in Thailand. Based on a sequential explanatory mixed-methods research design, a convenience sampling technique was employed to select 187 participants, from three large schools in Bangkok and three schools outside Bangkok, who completed the Likert scale questionnaire. The semi-structured interview was conducted face-to-face at the second stage with six students from two schools. The quantitative findings revealed that their perceived learner autonomy was, on average, at a high level. The thematic content analysis of the interview data generated four themes to verify the quantitative results and to determine the factors for such high autonomy, i.e. the importance of English for future career goals, self-study of English beyond the classroom, preference for communicative learning, and the impacts of teachers and peers on autonomy development. Theoretical and pedagogical implications were discussed, and further research was recommended.